Insulin induces a progressive increase in the resistance of subcutaneous tissue to fluid flow: Implications for insulin pump therapy. Issue 3 (17th November 2021) - Regittnig, Werner; Tschaikner, Mathias; Tuca, Alexandru‐Cristian; Simic, Amra; Feiel, Jürgen; Schaller‐Ammann, Roland; Licht, Alexander H.; Jungklaus, Miró; Pieber, Thomas R.
Abstract: Aim: To determine the effect of insulin on the resistance of subcutaneous tissue to the flow of infusion fluids. Materials and methods: Thirty subjects with type 1 diabetes wore two Accu‐Chek Spirit Combo insulin pumps with Accu‐Chek FlexLink infusion sets (Roche Diabetes Care, Mannheim, Germany) for 7 days. One pump was filled with insulin aspart (Novo Nordisk, Bagsvaerd, Denmark) and used for continuous subcutaneous insulin infusion (CSII). The other pump was filled with insulin diluting medium (IDM; Novo Nordisk) and used to deliver IDM subcutaneously at rates identical to those employed for CSII. Both infusion sites were assessed daily by measuring the pressure required to infuse various bolus amounts of IDM. Results: On day 1, maximum pressure (Pmax ) and tissue flow resistance (TFR; calculated from measured pressure profiles) were similar for both infusion sites ( P > 0.20). During the subsequent study days, the Pmax and TFR values observed at the IDM infusion site remained at levels comparable to those seen on day 1 ( P > 0.13). However, at the site of CSII, Pmax and TFR progressively increased with CSII duration. By the end of day 7, Pmax and TFR reached 25.8 */2.11 kPa (geometric mean */geometric standard deviation) and 8.64 */3.48 kPa*s/μL, respectively, representing a remarkable 3.5‐ and 20.6‐fold increase relative to the respective Pmax and TFR values observed on day 1 ( P < 0.001). Conclusion: Our results suggest that insulin induces a progressive increase in the resistance of subcutaneous tissue to the introduction of fluid; this has important implications for the future design of insulin pumps and infusion sets.